The Effect of Mouthwashes on Surface Hardness of Dental Ceramics - Jafari K; Hekmatfar S; Badakhsh S (Shiraz University of Medical Sciences, 2014)
Statement of problem: The effect of different mouthrinses on the surface characteristics of ceramic materials is not documented. Objectives: The aim of this study was to determine the effect of three mouthrinses, containing either alcohol, hydrogen peroxide or fluoride, on microhardness of two dental ceramics, (Duceram love, IPS e.max Ceram). Materials and Methods: Eighty cylindrical disks were prepared and divided into eight experimental groups (n=10 for each group) according to the ceramic material and storage solutions. The microhardness of each sample in all groups was recorded prior to testing. For each ceramic, three groups were immersed in one of the three mouthrinses for a total of 24 and 96 hours. The fourth group was immersed in distilled water as the control. At the end the specimens were taken out, rinsed, dried and tested using microhardness tester. Results: The results of the two-way ANOVA indicated that there was no interaction between media, time and materials (P>0.05). Microhardness of the ceramics was not adversely affected by immersion in the studied mouthrinses. Conclusions: The patients with porcelain restorations should be assured that using mouthrinses containing hydrogen peroxide, alcohol or fluoride do not damage the surface hardness of the porcelain.